Edukasi Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Bagi UMKM di Kabupaten Siak - Alfiati Silfi; Poppy Nurmayanti M; Eka Hariyani; Nita Wahyuni; Rosmayani Rosmayani (CANANG: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to provide education to Micro, Small, and Medium Enterprises (MSMEs) in Siak Regency regarding the preparation of financial reports in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The lack of understanding of MSMEs regarding the importance of systematic and standardized financial records is an obstacle to accountable and sustainable business management. Through training and mentoring, participants are given an understanding of basic accounting concepts, financial report structures, and practical steps in preparing reports based on SAK EMKM. The methods used in this activity include delivering materials, interactive discussions, and financial report preparation simulations with 20 participants. The results of the activity showed an increase in participants' understanding and ability in preparing simple financial reports that meet standards. This education is expected to help MSMEs in increasing financial transparency and access to formal financing.